Towards Better Numeracy Outcomes: Analyzing Factors and Interventions for Indonesian Students - Rudi Susilana; R. Nadia Hanoum; Della Amelia; Mohammad Ali; Norazrena Abu Samah (Universitas Syiah Kuala, 2024)
Numeracy is essential in many aspects of daily life, yet it remains a growing concern among Indonesian students. Numerous factors contribute to this issue, which must be addressed through pedagogical and psychological approaches. Correspondingly, this research had two main objectives: First, to describe students' performance in basic numeracy skills and the factors that hindered their development, and second, to analyze and map the learning activities students needed to improve their numeracy skills. To achieve these objectives, an ex post facto research design with a quantitative approach was employed. A total of 506 secondary school students from various regions in Indonesia (Female = 285; Male = 221) participated in this study. The sample was collected using a simple random sampling technique. Data was gathered via an online survey of 51 structured questions administered to the students. Multiple statistical tests were conducted to analyze the data, including descriptive statistics (mean scores) and inferential statistics (factor analysis). The findings indicated that the overall mean score for students' basic numeracy skills was moderate, with female students outperforming male students. Additionally, several factors hindered students' mastery of basic numeracy. The study also highlighted the need for more differentiated instruction, where students could receive personalized support based on their unique challenges and learning preferences.